STRATEGIES FOR BUILDING MILLENNIAL GENERATION HOUSES WITH SHARIA FINANCIAL PLANNING - Titania - Mukti; Nur Zidta Oktarinanda (Universitas Islam Indonesia, 2023)
Millennials generation find it difficult to own a home because of their consumptive lifestyle and houses have prices that are getting more expensive over time that are disproportionate to their income. In fact, many of them are desperate to buy a house with a credit system with high interest and and that credit has a repayment period up to tens of years, even though this can trigger financial problems. Therefore, this study aims to explain that Islamic financial planning give solution strategies to young people with low incomes can realize to owning their dream house without usury. This type of research is qualitative research with literature study method. The results of this study explain the design of a strategy in managing the income of a young couple for consumption needs, paying for temporary house rent, paying for electricity, water, wifi, emergency funds and investing in sharia instruments namely gold investment. Gold is resistant to inflation. The gold investment strategy of one gram per month can be collected for seven years which can be used to start building a dream house. This research is complemented by a strategy for choosing suitable land to live in and a strategy for building houses with gradual progress for seven years.